2023
DOI: 10.1126/sciadv.adh5598
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation by the NSL complex enables diversification of IFT functions in ciliated versus nonciliated cells

Tsz Hong Tsang,
Meike Wiese,
Martin Helmstädter
et al.

Abstract: Members of the NSL histone acetyltransferase complex are involved in multiorgan developmental syndromes. While the NSL complex is known for its importance in early development, its role in fully differentiated cells remains enigmatic. Using a kidney-specific model, we discovered that deletion of NSL complex members KANSL2 or KANSL3 in postmitotic podocytes led to catastrophic kidney dysfunction. Systematic comparison of two primary differentiated cell types reveals the NSL complex as a master regulator of intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 97 publications
(157 reference statements)
0
1
0
Order By: Relevance
“…In the DCC, MOF is thought to acetylate H4K16 with high specificity, a feature that appears to be conserved in human MSL complexes ( 19 , 27 ). However, as part of the NSL complex, MOF has been reported to acetylate H4K5, K8 and K12 ( 19 , 22 ). This notion is supported by a systematic analysis of KAT activities in female Drosophila cells, which showed that depletion of the key NSL subunit NSL1 leads to reduced H4K5ac (and statistically not robust K8ac) in addition to lower H4K16ac ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the DCC, MOF is thought to acetylate H4K16 with high specificity, a feature that appears to be conserved in human MSL complexes ( 19 , 27 ). However, as part of the NSL complex, MOF has been reported to acetylate H4K5, K8 and K12 ( 19 , 22 ). This notion is supported by a systematic analysis of KAT activities in female Drosophila cells, which showed that depletion of the key NSL subunit NSL1 leads to reduced H4K5ac (and statistically not robust K8ac) in addition to lower H4K16ac ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…KAT8 also plays a pivotal role in T-cell maturation, where its deletion leads to severe defects in T-cell receptor rearrangement and a consequential increase in genomic instability [47]. The NSL complex, particularly through its components KANSL2 and KANSL3, is essential for the transcriptional regulation of intraciliary transport genes that influence cilia assembly and microtubule dynamics [48]. This regulatory activity is crucial for cellular differentiation, which impacts kidney health, by maintaining podocyte function, as the deletion of KANSL2 or KANSL3 in podocytes leads to severe kidney dysfunction [48].…”
Section: Kat8's Role In Stem Cell Identity and Differentiationmentioning
confidence: 99%
“…The NSL complex, particularly through its components KANSL2 and KANSL3, is essential for the transcriptional regulation of intraciliary transport genes that influence cilia assembly and microtubule dynamics [48]. This regulatory activity is crucial for cellular differentiation, which impacts kidney health, by maintaining podocyte function, as the deletion of KANSL2 or KANSL3 in podocytes leads to severe kidney dysfunction [48]. Furthermore, studies show that KAT8 influences acute myeloid leukemia (AML) differentiation by suppressing MN1 (meningioma 1) expression, a gene associated with rapid leukemia onset when overexpressed [49].…”
Section: Kat8's Role In Stem Cell Identity and Differentiationmentioning
confidence: 99%